IDENTIFICATION OF GREEN ALGAE (CHLOROPHYTA) GENUS HALIMEDA IN THE WATERS OF MABA DISTRICT, EAST HALMAHERA - Ananda, Wilya; Amri, Khairul; Supriadi, Supriadi; Yasir, Inayah (Hasanuddin University, 2024)
Halimeda is a genus of calcified alga that inhabits tropical aquatic environments. The presences of Halimeda is essential for waters around mining sites, such as the waters of Maba District, wich is the center of mining in East Halmahera. As a calcareous organism, Halimeda functions as a buffer to neutralize the pH of waters. Although the presence of Halimeda in waters is not rare, studies on Halimeda taxonomy in Indonesia are very limited. Identification of Halimeda species can be done by looking at morphological and anatomical structures as an alternative based on the key to determining Halimeda species in the Indo-Pacific by Hillis & Collinvaux (1980), in addition to looking at DNA sequences. This study was aimed at identifying Halimeda species distributed in the waters of Maba District, East Halmahera based on morphological and anatomical characteristic. Besides, it also aims to determine the distribution and similarity of species between sampling locations. Sampling was carried out using purposive sampling method. Halimeda sample collection was prepared before identification. Eight species of Halimeda were found from four sampling sites, namely Halimeda cylindracea, H. distorta, H. macroloba, H. opuntia, H. simulans, H. discoidea, H. melanesica, and H. tuna. In additional to these eight species, seven unidentified Halimeda species were also found based on morphological and anatomical characteristc. Most similarity percentage of Halimeda species was found between Tanjung Buli-Monoropo at 75% and the lowest between Gee Island-Pakal Island (0%). The distribution of Halimeda species in waters in influenced by many factors, including substrate type, nutrients, light intensity, salinity, pH, temperature, depth, wave and current action.